Design of a New Cryptographic Hash Function – Titanium - Mohammad A. AlAhmad (Institute of Advanced Engineering and Science, 2018)
This paper introduces a new cryptographic hash function that follows sponge construction. Paper begins with outlining the structure of the construction. Next part describes the functionality of Titanium and cipher used. A competition between block cipher and stream cipher is presented and showed the reason of using block cipher rather than stream cipher. Speed performance is calculated and analyzed using state-of-art CPUs.